Effect of pH on the cation exchange capacity of some halloysite nanotubes. (2nd January 2018) - Gray, Nia; Lumsdon, David G.; Hillier, Stephen
Abstract: The cation exchange capacity (CEC) of seven well characterized halloysite nanotubes (HNTs) in the dehydrated 7 Å form has been measured using a method based on cobalt hexammine exchange. In addition to unbuffered measurements, which varied between 2.9 and 9.3 cmol(+)kg −1, CECs were also determined over a wide pH range and proton titration measurements were conducted on two samples. The data were fitted using a constant capacitance model based on the presence of two sites: permanently charged sites and pH-dependent variable charged sites. Normalization of CEC to the average specific surface area (BET) of the halloysite samples reduces considerably the variation of CEC values for the different samples particularly over the intermediate pH range (5–9) with the average value at pH 7 equal to 8.5 cmol(+)kg −1 and a standard deviation of 1.17. Overall the CEC behaviour of the seven samples appears reasonably consistent throughout the set. Calculations based on proton titrations suggest a ratio of variable charge to basal sites for the dehydrated halloysite nanotubes of ∼3:1.